Türkiye’nin Kuzey Irak Politikası 1986-1996 - Ant, Serdar (My University, 1999)
The purpose of this study is to make an analysis of Turkish foreign policy in northern Iraq in the post-cold war era by focusing on the developments in the Gulf Crisis. It can be stated that one of the most important problems of Turkey after the Cold War has been the issue of redefinig itself, particularly its foreign policy in the new international environment which took place as a result of the collapse of communism, the dissolution of Warsaw Pact and the disintegration of Union of Soviet Socialist Republics (USSR). It is clear that there is a close relationship between a country's domestic political dynamics and international settings. They influence each other and define each other's limits and possibilities. From this point of view, it can be argued that, in 1990s , internationalist and nationalist foreign policy vision have been competing to establish the direction of Turkish foreign policy in the emerging new world order. However, it will not be so true to claim that effects of the developments in international environment have remained limited with only the sphere of foreign policy. It is apparent that the events which occurred in the world politics in the beginning of the 90s are descriptive in initiating the discussions focusing on the social and political structure of Turkey. Thus, it seems that the nationalist-internationalist dichotomy is getting clear within the framework of the new strategies adopted by the Western Pact, or -in particular- by the USA, in the post-cold war era on the axis of the role given to Turkey and the Turkey's foreign policy in northern Iraq. In this context, existence of Kurdish issue, which Turkey has not been able to overcome since the mid 80s, has been producing problems in both internal and external affairs of Turkey. Kurdish issue, which has also an external dimension stemming from the power vacuum in northern Iraq particularly since 1991, can be considered as the dilemma of Turkish foreign policy in the new world order. In fact, the different approaches about Turkish foreign policy towards northern Iraq reflect the differences in the solution of Kurdish issue . During the period, the fact that the 1991 Gulf Crisis has become an Iraq Crisis and continuity of the crisis makes Turkey's foreign policy in northern Iraq open to foreign interventions. In other words, it has been more difficult for Turkey to pursue a foreign policy on behalf of its own national interests in northern Iraq because of its own Kurdish issue. On the other hand, the power vacuum in northern Iraq has also been playing a hardening role on Kurdish issue in Turkey. In the context of what is expected from Turkey in the new world order in the axis of Middle East- Caucasus-Central Asia, Kurdish question, which, essentially, is a socio-economic issue exploited by regional and other foreign powers in addition to underdeveloped character of the Turkey's southeastern region rather that a national question, and northern Iraq issue will have a considerable importance as the context of the Turkey's domestic politics and problems. Turkey's foreign policy towards northern Iraq during the Gulf Crisis, during which Kurdish issue also began to internationalize, and bifurcation in implementation of the policy constitutes the focus of this study. It is observed that the United States wanted Turkey to recognize and support the establishment of a Kurdish state in the northern Iraq since the Gulf War. In this context, there seem to be two options with regard to northern Iraq. The first one is the establishment of a Kurdish state under Turkey's protection and supervised by the USA and the second one is the cooperation among countries in the region and Kurdish organisation to refuse the US initiative and find solution together. Therefore, the effects of the USA and its plans towards northern Iraq have to be taken into consideration in examining the decision making process of the Turkish foreign policy in northern Iraq. One of the aims of this study is to examine the US' effects on Turkish foreing policy towards northern Iraq and to clarify the bifurcation in the foreign policy decision-making process of Turkey in this context , particularly in the period of 1990-91 Gulf Crisis.

Bu çalışmanın amacı, Soğuk Savaş sonrası dönemde Türkiye'nin Kuzey Irak politikasının çözümlemesini yapmaktır. Soğuk Savaş sonrasında komünizmin çöküp, Sovyetler Birliği ve Varşova Paktı'nın dağıldığı uluslararası ortamda, Türkiye'nin en önemli dış politika problemlerinden birinin kendini, özellikle de dış politikasını, yeniden tanımlama sorunu olduğu söylenebilir. Bir ülkenin kendi iç politik ortamı ile uluslararası ilişkilerin dinamizmi arasında doğrudan bir ilişki olduğu ; bu karşılıklı ilişkinin bazı sınırlamalar ve olanaklar getirdiği inkar edilemez. Bu perspektiften bakıldığında, 90'lı yıllarda ulusalcı ve uluslararasıcı (enternasyonalist) dış politika eğilimlerinin Türkiye'nin dış politikasının yönünü belirlemede çatıştıkları görülmektedir. Bununla beraber, uluslararası ortamdaki gelişmelerin etkisinin sadece dış politika alanı ile sınırlı kaldığını iddia etmek de pek doğru olmayacaktır. 90'ların başında Türkiye'nin sosyal ve siyasal yaşamı üzerine yapılan tartışmalarda uluslararası ilişkilerdeki gelişmelerin de etkili olduğu açıktır. Bu ulusalcı-uluslararasıcı ikilemi, Soğuk Savaş sonrası dönemde, Balkanlar-Kafkaslar-Ortadoğu ekseninde Batı , özellikle de ABD, tarafında Türkiye'ye biçilen rol ve Türkiye'nin Kuzey Irak'a yönelik dış politikası bağlamında açıklık kazanmaktadır. Bu bağlamda, Türkiye'nin 80'lerin ortasından beri bir türlü üstesinden gelemediği Kürt sorunu hem iç hem de dış politikayı etkileyen sonuçlar yaratmaktadır. 1991'den beri Kuzey Irak'taki otorite boşluğundan kaynaklanan bir dış boyuta da sahip olan Kürt sorununun, Yeni Dünya Düzeninde Türkiye'nin en önemli dış politika maddelerinden biri olduğu söylenebilir. Aslında, Türkiye'nin Kuzey Irak'a yönelik dış politikasındaki değişik yaklaşımlar, Türkiye'nin kendi Kürt sorununu çözme konusundaki yaklaşım farklılıklarını da yansıtmaktadır. Ayrıca, Körfez Savaşı'nın bir Irak Krizine dönüşmesi ve bunun kalıcılık kazanması Türkiye'nin Kuzey Irak politikasını da dış müdahalelere açık hale getirmektedir. Diğer bir deyişle, Türkiye'nin Kuzey Irak'ta kendi çıkarları doğrultusunda bir dış politika izlemesi her geçen gün daha da zorlaşmaktadır. Öte yandan, Kuzey Irak'taki otorite boşluğu da Türkiye'nin kendi Kürt sorunu üzerinde olumsuz etkiler yaratmaktadır. Soğuk Savaş sonrası, Balkanlar-Kafkasya-Ortadoğu ekseninde Türkiye'ye verilen rol bağlamında, aslında hem bölgesel hem de dış güçler tarafında kullanılan, temelde ulusal olmaktan çok sosyo-ekonomik karakterdeki bir sorun olarak nitelenebilecek Kürt sorunu dikkate değer bir önem kazanmaktadır. Kürt sorununun uluslararası bir boyut kazanmaya başladığı Körfez Krizi dönemindeki Türkiye'nin Kuzey Irak'a yönelik dış politikası ve bu politikanın uygulanmasında ortaya çıkan çatallaşma bu çalışmanın ana eksenini oluşturmaktadır. ABD'nin, Körfez Krizi'nden beri, Kuzey Irak'ta kurulacak bir Kürt devletinin, Türkiye tarafından tanınmasını ve himaye edilmesini istediği görülmektedir. Bu bağlamda, Türkiye'de iki yaklaşım dikkati çekmektedir : Birincisi, Türkiye'nin himayesinde, ABD tarafından denetlenecek bir Kürt devletinin kurulmasını benimseyen anlayıştır. Diğeri ise, ABD girişimlerini reddederek, bölge ülkeleri ve Kürt örgütleri ile işbirliği çerçevesinde soruna ortak bir çözüm bulmayı esas alan görüştür. Dolayısıyla, ABD ve Kuzey Irak konusundaki planları, Türkiye'nin Kuzey Irak'a yönelik dış politika yapım sürecinde dikkate alınması gereken önemli unsurlardandır. Bu çalışmanın amaçlarından biri de, ABD'nin Türkiye'nin Kuzey Irak politikası üzerindeki etkilerinin incelenmesi ve bu bağlamda, Türk dış politikasındaki çatallaşmanın, özellikle 1990-91 Körfez Krizi dönemi esas alınarak, aydınlatılmasıdır.
Keywords: Dış Ilişkiler-türkiye